Analisis Kinerja Realisasi Anggaran Dalam Belanja Daerah Pemerintah Probolinggo - Nur Hasanah; Elok Dwi Vidiyastutik (Ecobuss, 2018)
The research was conducted at the Regional Revenue, Financial and Asset Management Agency (BPPKAD) of Probolinggo City with the aim of analyzing the performance of the budget realization in the regional expenditure of the Probolinggo City Government. the type of research used is quantitative descriptive, the data used from the 2013-2017 fiscal year. The results show the difference between the budget and the realization of spending has a significant difference when seen from the nominal, for growth is always changing or not, for harmony analysis for the last period shows improvement in realizing shopping spending, and for the calculation of shopping efficiency ratios of in 2013 to 2017 the City of Probolinggo Government has made savings which resulted in a SILPA surplus (Over Time Budget Calculation) which is good to use the following year. Keywords: Performance, Budgets Realization, and Regional Expenditures